PENGEMBANGAN E-MODUL BERBANTUAN BOOKCREATOR PADA MATERI BAGAIMANA BENTUK INDONESIAKU - Marisa; Elly Sukmasana; Rini Sri Indriani (STKIP Subang, 2024)
Marisa 037120063. This research aims to develop a product and determine the feasibility of an e-module assisted by Bookcreator on the material on the Form of Indonesia for class V at SDN Kedung Badak 2, Bogor City, even semester of the 2023/2024 academic year. The method used in this research is Research and Development (R&D) with the ADDIE model. In perfecting the e-module product with the help of Bookcreator on the material of what Indonesiaku looks like, validation tests have been carried out with material experts, language experts and media experts. The results obtained were that the final validation value from the material expert was 98%, which means it is very good and can be used, the final result from the language expert was 95.6%, which means it is very good to use, then finally the final result from the media expert was 86%, which is meaning it is very good to use. The results of the trial on 19 students in class V-B showed that the e-module development with the help of Bookcreator on the material on how to form Indonesiaku had a feasibility value of 89%, which means it was very good for students to use in learning and had a teacher response value of 92% which was meaning it is very good to use. Therefore, it can be concluded that the development of ADDIE (Analysis, Design, Development, Implementation, Evaluation) was declared very valid by the three validators with a score of 98% from material experts, 96.6% from language experts, 86% from media experts, 89 % of student responses, and 92% of teacher responses, from these results there is an average result of 92% of the total.